Utilizing Smartphone ECG for Early Detection and Management of Ischemic Heart Disease: A Case Report - Singh, Yogendra; Pandey, CB; Chandola, Nitin; Agarwal, Deeksha (Journal of Cardiology and Cardiovascular Medicine, 2024)
Ischemic Heart Disease (IHD) remains a significant cause of morbidity and mortality worldwide. We present a case report of a 54-year-old individual presenting with symptoms suggestive of IHD, including palpitations and chest heaviness. Utilizing a Spandan device at home, the patient detected anteroseptal and lateral wall ischemia, prompting consultation with a cardiologist. Subsequent diagnostic evaluations revealed Left Ventricular Hypertrophy (LVH), concentric LVH, regional wall motion abnormality, and Grade I diastolic dysfunction. Hypertension and dyslipidemia were identified as prominent risk factors, with additional findings of carotid artery disease. Management strategies included antihypertensive medications, lipid-lowering therapy, and lifestyle modifications. This case underscores the complexity of diagnosing and managing IHD, highlighting the importance of comprehensive assessment and multidisciplinary care in optimizing patient outcomes.